COMPOSITION, STRUCTURE AND BIODIVERSITY OF TREES IN TROPICAL MONTANE CLOUD FOREST PATCHES IN SERRA DO PAPAGAIO STATE PARK, SOUTHEAST BRAZIL. (19th April 2018) - Ribeiro, J. H. C.; Santana, L. D.; Carvalho, F. A.
Abstract : Tropical montane cloud forests (TMCFs) are characterised principally by frequent immersion in ground-level clouds, which influences their structure. This study aimed to characterise TMCFs in Serra do Papagaio State Park, Minas Gerais State, Southeast Brazil, and to test the hypothesis that TMCF areas can be highly heterogeneous by comparing the tree species composition and structural parameters of 10 TMCF patches in the studied landscape. TMCFs of Serra do Papagaio State Park are of particular interest for conservation, because they contain important populations of threatened tree species.